2007
DOI: 10.2337/db07-0670
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia Rapidly Increases Human Muscle Microvascular Perfusion but Fails to Increase Muscle Insulin Clearance

Abstract: OBJECTIVE-Transport of insulin from the central circulation into muscle is rate limiting for the stimulation of glucose metabolism. By recruiting muscle microvasculature, insulin may promote its own movement into muscle interstitium. We tested whether in humans, as in the rat, insulin exerts an early action to recruit microvasculature within skeletal muscle. We further hypothesized that expansion of the microvascular volume of muscle would enhance muscle insulin clearance.RESEARCH DESIGN AND METHODS-Microvascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 50 publications
7
97
1
Order By: Relevance
“…In response to both exercise and insulin, GLUT4 translocation to the muscle membrane is accelerated (21,74), while the ability to phosphorylate glucose may be unaffected or inhibited by G6P. In addition to the effects on glucose transport, exercise and insulin increase muscle capillary blood flow (12,20,44,87). Together these cellular events predict a shift in the barrier from transport to phosphorylation.…”
Section: Distributed Control Of Blood Glucose Removalmentioning
confidence: 99%
“…In response to both exercise and insulin, GLUT4 translocation to the muscle membrane is accelerated (21,74), while the ability to phosphorylate glucose may be unaffected or inhibited by G6P. In addition to the effects on glucose transport, exercise and insulin increase muscle capillary blood flow (12,20,44,87). Together these cellular events predict a shift in the barrier from transport to phosphorylation.…”
Section: Distributed Control Of Blood Glucose Removalmentioning
confidence: 99%
“…However, as discussed above, even after several hours of hyperinsulinemia, the insulin concentration in the muscle interstitium did not approach plasma concentrations. This would suggest that transport by the endothelium is in fact the limiting process and responsible for the decline in insulin clearance as insulin concentration increases (28).…”
Section: How Does Insulin Exit the Vasculature?mentioning
confidence: 99%
“…We have measured the rate of insulin transport into human forearm skeletal muscle both in the fasting state and during a euglycemic insulin clamp by combining arterial/venous sampling with measurements of forearm blood flow (28). These studies indicated that 10 -15% of the insulin entering muscle with arterial plasma is removed in a single pass at fasting levels of insulin.…”
Section: How Does Insulin Exit the Vasculature?mentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin stimulates microvascular recruitment to facilitate delivery of glucose and insulin to the myocyte to enhance glucose disposal [6][7][8][9][10]18]. Insulin resistant rats [3] and obese humans [15,16] also display marked reductions in insulin-mediated microvascular recruitment and insulin-mediated muscle glucose uptake suggesting that the loss of muscle perfusion may contribute to the insulin resistance.…”
Section: Introductionmentioning
confidence: 99%